Employee Mobility and Innovation - Novrys Suhardianto, - (Primrose Hall Publishing Group, 2020)
This study aims to investigate the effect of employee mobility constraint through inevitable disclosure doctrine (IDD) adoption by U.S. state courts on firms' innovation. IDD adoption serves as an exogenous shock on the labour market and industry competition from which this study expects the negative effect on firms' innovation comes. This study uses U.S. firms and measures innovation using R&D expenditure and patent registration and citation. This study finds that employee career constraints through IDD adoption reduces industry competition. The deteriorating effect of IDD enactment on innovation is not only for the initial adoption period but also for at least one year ahead. The negative impact of employee mobility constraint is due to the decrease in market competition. This research suggests that the relaxation of market monitoring on managers will decrease the performance of the firm.